Faces of Anorexia in Adolescents: Diagnosis, Risk, and Support - Julia Natalia Skibicka; Kamila Rosińska; Ewelina Justyna Janicka; Mateusz Rosiński; Monika Niedźwiedzka (Quality in Sport)
Introduction: Anorexia nervosa (AN) is an eating disorder most commonly occurring during adolescence, characterized by the highest mortality rate among mental health conditions. It is a serious disorder affecting the physical and psychological development of children and adolescents. The increase in AN cases following the COVID-19 pandemic and difficulties in its early diagnosis present significant challenges in treatment.